A Hospital Based Seropositivity For Hepatitis B Surface Antigen And Antibodies To Hiv In And Around Puducherry – A Retrospective Study - SUNIL SHIVEKAR; SMITA SHIVEKAR; PRACHI SABAN; PRIYADHASHANI A; R. GOPAL (International Journal of Pharma and Bio Sciences, 2012)
Background: Studies across the country have reported a decline in the rate of HIV and HBsAg in the urban population and there is a lack of data on rate and pattern of theses infections in the rural part. To conduct community based seroprevalence studies, funds, facilities and man power are required. Clinical data collected by hospitals can help in estimating the disease burden due to these viruses in the community. In this backdrop, the present study was designed to estimate the seropositivity for these viruses in a hospital based population. Materials and Methods: Patients reporting to this hospital with various diagnoses, who were advised to undergo HIV and HBsAg testing, were included in this study. The HIV testing was done as per the NACO guidelines and HBsAg was confirmed with two different tests. All the data was analysed by Chi -square test. Results: A year wise seropositivity showed significant decline in HIV and HBsAg cases from this part of the country. The overall seropositivty for HIV and HBsAg was 1.25% and 2.0% respectively. Male predominance was observed with maximum positivity among the active age group. Maximum positivity rate of 76% and 74% for HBsAg and HIV was reported from Villupurum district. Conclusion: The present study shows a decline in the seropositivity for HIV and HBsAg in the rural population in and around Puducherry, which also indicates the level of awareness about these viruses in community. It also highlights the use of hospital based seropositivity studies as an option for community based studies.